Impact of corporate governance on financial performance among government - link companies in Malaysia and Singapore - Shanmugaretnam, Shubatra; David, Ng Ching Yat; Yen, Wen Chang; Low, Suet Cheng (UiTM Cawangan Johor, 2023)
The aim of this research was to investigate the impact of Corporate Governance on financial performance among Government Link companies in Malaysia and Singapore as a comparative study for a period of 15 years from 2005 to 2019. A sample of 60 Government-Link companies consisting of 34 from Malaysia and the balance 26 from Singapore was taken. A total of 900 firm years was observed. Panel data analysis using EViews was carried out to examine the effect of Corporate Governance components which compromise the percentage of independent directors, the percentage of independent directors on the audit committee, the frequency of board meetings and the composition of women directors, effect on firm performance. Tobin 's Q was used as the measurement for firm performance. The outcome from this research indicated that Corporate Governance in Malaysia Government-Link Companies have a greater effect on financial performance compared to Singapore Government-Link Companies. In summary, this study has been beneficial by providing an understanding of Corporate Governance practices to stakeholders, policy makers, shareholders, Board of Directors of Government-Link Companies and the government itself